Decreasing subthalamic deep brain stimulation frequency reverses cognitive interference during gait initiation in Parkinson's disease. Issue 11 (November 2018) - Varriale, Pasquale; Collomb-Clerc, Antoine; Van Hamme, Angele; Perrochon, Anaik; Kemoun, Gilles; Sorrentino, Giuseppe; George, Nathalie; Lau, Brian; Karachi, Carine; Welter, Marie-Laure
Highlights: High and low-frequency STN-DBS improve gait initiation in PD in absence of cognitive interference. High-frequency STN-DBS alters gait initiation during cognitive loading context. Low-frequency STN-DBS preserves gait initiation when coupled with cognitive load. Abstract: Objective: Freezing of gait (FOG) represents a major burden for Parkinson's disease (PD) patients. High-frequency (130-Hz) subthalamic deep-brain-stimulation (STN-DBS) has been reported to aggravate FOG whereas lowering the frequency to 60–80 Hz improves FOG. To further understand the effects of STN-DBS on FOG, we assessed the effects of 80-Hz and 130-Hz STN-DBS on gait initiation performance, in relation to motor and executive function processing. Methods: Gait initiation was recorded in 19 PD patients and 20 controls, combined or not with a cognitive interference task with a modified Stroop paradigm. PD patients were recorded before surgery with and without dopaminergic treatment, and after surgery with 80-Hz and 130-Hz STN-DBS in a randomised double-blind crossover study. Results: In the absence of cognitive interference, PD patients exhibited significant gait initiation improvement with dopaminergic treatment, 80-Hz and 130-Hz STN-DBS. Nine patients performed the cognitive interference task. With 130-Hz STN-DBS, all gait initiation parameters were significantly degraded, whereas the cognitive interference task induced no major changes before surgery and with 80-Hz STN-DBS, as in controls. Conclusions: High-frequency STN-DBS leads to an inability to simultaneously process motor and cognitive information while this ability seems preserved with low-frequency STN-DBS. Significance: This study supports the potential benefit of 80-Hz STN-DBS on FOG.